Exploring The Interplay of Perception, Motivation, Tax Knowledge, Professional Recognition, Work Environment, and Parental Support on Career Interest in Taxation - Sariningsih, Eka; Yuliana, Yuliana; Hildayanti, Maida (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2025)
experts. This study aims to investigate the Accounting students' perception about their interest in working in the taxation sector. Several factors were examined related to perception, motivation, tax knowledge, professional recognition, work environment, and parental support. This study uses a quantitative approach. The population in this scientific work is active students of the Accounting study program at the Faculty of Economics and Management, Malahayati University, who have taken or studied taxation courses. The sample of this study was 123 students. Data collection techniques using questionnaires. The sampling method was purposive sampling with a total of 100 respondents who were studying taxation.  Using the analysis technique, the Partial Least Squares (PLS) method for hypothesis testing.  The findings reveal that Perception, Motivation, and Parental Support influence Interest in Working in the Taxation Sector. However, Tax Knowledge, Professional Recognition, and Work Environment have an insignificant influence, meaning they do not have much impact on Interest in Working in the Taxation Sector. Understanding these dynamics can help educational institutions and employers better tailor their outreach and support strategies to attract talent into the taxation field.